The influence of social support on psychological well-being in early adult women after experiencing a breakup in Semarang City - Anisa Atika Putri; Siska Adinda Prabowo Putri; Brigitan Argasiam (Jurnal Psikologi Tabularasa, 2025)
This study aims to analyze the effect of social support and forgiveness on psychological well-being in early adult women after experiencing a breakup. This type of research is quantitative cross-sectional using purposive sampling technique. The sample characteristics in this study are adult women aged 18-40 years who have experienced a breakup for at least one year. The number of respondents was 542 participants. This research instrument uses a social support scale, based on the theory of Zimet, dkk. (1998) with a reliability result of 0.904. The pemaafan scale is based on McCullough’s (2000) theory with a reliability result of 0.928. The data analysis technique uses multiple linear regression analysis method by showing that there is a simultaneous influence between social support and pemaafan. The amount of social support and pemaafan variables can affect psychological well-being in adult women by 47.8% with the remaining 52.2% influenced by other factors.